Canadian-American Jurisprudence on "Good Faith" Bargaining - Bemmels, Brian; Fisher, E.G.; Nyland, Barbara (Relations industrielles / Industrial Relations, 1986)
Canadian-American Jurisprudence on « Good Faith » Bargaining